Characterization of a heparin-binding site on the catalytic domain of factor XIa: Mechanism of heparin acceleration of factor XIa inhibition by the serpins antithrombin and C1-inhibitor - Yang, Likui (2009)
Heparin accelerates inhibition of factor XIa (fXIa) by the serpins antithrombin (AT) and C1-inhibitor (C1-INH) by more than two orders of magnitude. The mechanism of the heparin-mediated acceleration of fXIa inhibition by these serpins is incompletely understood, as heparin appears to interact with both the catalytic and non-catalytic domains of the protease. We replaced the basic residues of the fXIa 170-loop (Lys-170, Arg-171, Arg-173, Lys-175 and Lys-179 - chymotrypsin numbering) with Ala, using an expression system that allows separation of the fXIa catalytic domain (CD) from non-catalytic domains. Heparin-mediated inhibition of 170-loop CD variants with AT was impaired 3 to 10-fold relative to the wild type (CD-WT). In reactions with C1-INH, Arg-171 was the most critical residue contributing ∼2-3-fold to heparin-mediated inhibition of CD-WT. A template mechanism did not fully account for the effect of heparin with either serpin, as the second-order inhibition rate constants did not exhibit a characteristic bell-shaped dependence on heparin concentrations. Further studies revealed that the C1-INH inhibition of full length fXIa containing Ala substitutions for basic residues of the 148-loop is not enhanced by heparin. Inhibition by AT of a full-length fXIa variant containing an Ala substitution for Arg-37 in the fXIa CD was ∼5-fold greater than for wild type fXIa in the absence of heparin. These results suggest that basic residues of the fXIa 170-loop form a heparin-binding site, and that the accelerating effect of heparin on inhibition of fXIa by AT or C1-INH may be mediated by charge neutralization and/or allosteric mechanisms that overcome the repulsive inhibitory interactions of serpins with basic residues on the fXIa 148 and 37 loops.